THE ROLES OF INSTITUTIONS IN FIGHTING AGAINST POVERTY - Surjono Surjono (TATALOKA, 2015)
Decentralization and reformation in Indonesia have entered an uncertainty stage of people’s welfare in the near future. Uncertainty of political stability and fluctuative oil prices also led to uncertainty of other dimensions of development. This paper aims to elaborate the roles of institution in reducing poverty and identify indicators to evaluate the performance of pro-poor development, particularly in Indonesian context. The method was literature reviews and specific case study. Sustainable development indicators were employed to evaluate an appropriate strategies by comparing with best practices in several local governments in Indonesia. This paper promotes steps in reducing poverty and provides indicators of pro-poor governance. The result of analysis shows that development planning at local government should have balanced strategies with focus on indicators to accelerate poverty reduction in the regions.